Synthesis and development of light-activated molecular probes - Savage, M (2017)
Judicious addition of photolabile caging groups (PCGs) to protect biologically im- portant molecules, has enabled the development of many powerful chemical tools for the study of biological processes. These tools have the potential to be activated in a cellular setting by irradiation with light of appropriate wavelengths, restoring functionality, with excellent spatial and temporal control. This D. Phil. dissertation highlights two biologically relevant examples where PCGs can be applied: (i) 4,5-dimethoxynitrobenzyl (DMNB) caged derivatives of GSH and ESG, were synthesised and uncaging of the DMNB group at 350 nm to reveal the free α-carboxylic acid of the glycine residue was demonstrated. These molecules have the potential to probe the binding mode within the KefC KTN binding domain, a ligand-gated K+ efflux system, critical for bacterial response to electrophilic assault. The molecules are currently with collaborators awaiting further evaluation. (ii) The wavelength-dependent application of PCGs toward the study of protein post- translational modifications (PTMs) was developed. PTMs modulate protein function and have a ubiquitous role in a diverse range of cellular functions. A wavelength selective sequential pair of PCGs was developed and demonstrated in a tripeptide, using the diethylamino coumarin (DEACM), which was cleaved at 420 nm, and the DMNB caging group, which was subsequently cleaved at 350 nm. A chromatically orthogonal pair of PCGs, with possible applications in both organic synthesis and biological systems, incorporating the BODIPY-based and DEACM caging groups, which could be cleaved at 530 nm and 420 nm, respectively, was also developed. Photolysis was conducted on a tripeptide and hexapeptide and an in vitro application was demonstrated where when caged, the peptide was not susceptible to peptidolysis when incubated with enzymes. Following irradiation at 420 nm, the DEACM group was uncaged and the peptide underwent peptidolysis in the presence of Endoproteinase AspN, whereas following irradiation at 530 nm to uncage the BODIPY group, the peptide underwent peptidolysis in the presence of Endoproteinase LysC. These results not only provide conclusive evidence of the ability of this pair of caging groups to act in a wavelength orthogonal sense but also demonstrates the potential applicability of the pair to biochemical studies. This pair of PCGs represents the first example of an orthogonal pair of caging groups where both PCGs could be cleaved, at wavelengths longer than 400 nm, in a sequence independent manner.